THE RELATIONSHIP OF CERVICAL VERTEBRAL MATURATION (CVM) STAGE AND ANTEROPOSTERIOR FACIAL DIMENSIONS IN INDONESIAN POPULATION - MAHINDRA AWWALUDIN ROMDLON; Setiadi W Logamarta; Yulia Anggraeni (Berkala Ilmiah Kedokteran Duta Wacana, 2020)
Background: Growth and development are two different but interrelated and difficult to separate factors. The growth spurt in boys is different from girls. Facial growth is closely related to overall body growth, one of which is the growth of the cervical vertebrae. Objective: The objective of this study was to determine the anteroposterior dimensions of the face based on the maturation levels of cervical vertebrae in 12-14 years old children. Method: Quantitative research using an analytic observational method with a cross-sectional approach was conducted on 21 boys and 21 girls. Measurement of anteroposterior facial length (S-A' and PTM-A) and assessment of cervical vertebral bone maturation level using the Hassel and Farman method. Results: Independent t-test results showed that there was a significant difference (p